The Flexibility of Physio-Cognitive Decline Syndrome: A Longitudinal Cohort Study - Lin, Yi-Cheng; Chung, Chih-Ping; Lee, Pei-Lin; Chou, Kun-Hsien; Chang, Li-Hung; Lin, Szu-Ying; Lee, Yi-Jung; Lin, Ching-Po; Wang, Pei-Ning (Frontiers in Public Health, 2022)
The mutual presence of impairments in physical and cognitive function in older adults has been reported to predict incident disability, dementia, and mortality. The longitudinal transitions of phenotypes between these functional impairments, either individually or in combination, remain unclear. To investigate the natural course and the prevalence of physical impairments and/or cognitive impairments, we enrolled participants from a community-based population. Data from the first (August 2011 and December 2012) and second wave (August 2013 and June 2015) of the I-Lan Longitudinal Aging Study were retrieved. All participants were classified into four groups: robust, mobility impairment (MI), cognitive impairment (CI), and physio-cognitive decline syndrome (PCDS). The MI was diagnosed with weakness and/or slowness. The CI was diagnosed if subject met a cut off below 1.5 standard deviations of age-, sex- and education-matched norms of any neuropsychological assessments. The PCDS combined with MI and CI. Our results showed 38%, 14%, 30%, and 18% of participants in the robust, MI, CI, and PCDS at the first wave, respectively. After 2.5 years, 17% robust, 29% MI, and 37% CI progressed to PCDS. In contrast, 33% of PCDS was reversed to non-PCDS. The predictors of conversion to PCDS included worse memory and language functions, older age, lower muscle mass, and the presence of diabetes. In PCDS, a stronger hand-grip strength, younger age, and better memory functions predicted reversion to non-PCDS status. In summary, we probe the transition of PCDS. The skeletal muscle mass/function and memory function are crucial factors associated with the reversion or progression of PCDS.